2015
DOI: 10.1038/srep09738
|View full text |Cite
|
Sign up to set email alerts
|

Altered white matter integrity in individuals with cognitive vulnerability to depression: a tract-based spatial statistics study

Abstract: The microstructure of white matter in patients with major depressive disorder (MDD) has been demonstrated to be abnormal. However, it remains unclear whether these changes exist prior to the onset of disease. In this study, diffusion tensor imaging was used to evaluate white matter integrity in individuals who exhibited cognitive vulnerability to depression (CVD), MDD, and healthy controls (HC). Compared with the HC, MDD exhibited a lower fractional anisotropy (FA) in ten brain regions: the cerebral peduncle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 37 publications
4
16
0
Order By: Relevance
“…Therefore, reduced integrity of the external capsule, as observed in institutionally reared children, may be associated with reduced motivation and behavioral withdrawal, and contribute to higher scores of depression. Our findings are consistent with additional studies showing associations between lower integrity of the external capsule and higher depression symptoms in youth and adult samples (Guo et al, 2012, Bessette et al, 2014, Xiao et al, 2015). …”
Section: Discussionsupporting
confidence: 92%
“…Therefore, reduced integrity of the external capsule, as observed in institutionally reared children, may be associated with reduced motivation and behavioral withdrawal, and contribute to higher scores of depression. Our findings are consistent with additional studies showing associations between lower integrity of the external capsule and higher depression symptoms in youth and adult samples (Guo et al, 2012, Bessette et al, 2014, Xiao et al, 2015). …”
Section: Discussionsupporting
confidence: 92%
“…This FA increase is suggestive of changes in white matter structure, including fiber rearrangement. The majority of the evidence for white matter changes in depression is actually for decreased FA: this is the case for cingulum, as well as splenium of corpus callosum and external and internal capsules, in adults with (Xiao et al, 2015) and adolescents at risk of (Huang et al, 2011) depression.…”
Section: Metabolic and Structural Changes In Cps Micementioning
confidence: 99%
“…Several past preliminary studies found that alterations of the white matter, both in size and morphology, were associated with a diagnosis of depression (Nobuhara et al, ; Nobuhara et al, ; Taylor et al, ) and depression outcomes (Alexopoulos, Kiosses, Choi, Murphy, & Lim, ; Bae et al, ; Taylor et al, ). In fact, the white matter atrophy reported in patients with depression was accompanied by high white matter hyperintensities (WMH) on magnetic resonance imaging (MRI), which most likely represents white matter fiber dysmyelination (Aizenstein et al, ; Dalby et al, ), as well as by low fractional anisotropy (FA) on diffusion tensor imaging (DTI), which most likely represents decreased integrity of myelinated fibers in the white matter (Liu et al, ; Xiao, He, McWhinnie, & Yao, ). Furthermore, lesions of myelinated fibers in the white matter were positively correlated with the severity of depression (Iosifescu et al, ), and subjects with severe damage to myelinated fibers of the white matter had a poor response to antidepressants (Papakostas et al, ; Tham, Woon, Sum, Lee, & Sim, ), indicating that the myelinated fibers of the white matter may not only participate in the pathomechanism of depression but also play an extremely important role in the mechanism of antidepressant therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Several past preliminary studies found that alterations of the white matter, both in size and morphology, were associated with a diagnosis of depression (Nobuhara et al, 2004;Nobuhara et al, 2006;Taylor et al, 2004) and depression outcomes (Alexopoulos, Kiosses, Choi, Murphy, & Lim, 2002;Bae et al, 2006;Taylor et al, 2004). In fact, the white matter atrophy reported in patients with depression was accompanied by high white matter hyperintensities (WMH) on magnetic resonance imaging (MRI), which most likely represents white matter fiber dysmyelination (Aizenstein et al, 2011;Dalby et al, 2010), as well as by low fractional anisotropy (FA) on diffusion tensor imaging (DTI), which most likely represents decreased integrity of myelinated fibers in the white matter (Liu et al, 2016;Xiao, He, McWhinnie, & Yao, 2015).…”
mentioning
confidence: 99%